Anesthetic and hematological factors - Harguindeguy, Martín (Cirugía del Uruguay, 2002)
In the evaluation and treatment of these patients participates a multidisciplinary group that works in close relationship and communication facing changing situations and derived dynamics of the complexity offered by liver surgery resective.